Community Service The Importance of Improving Basic Life Support Through Emergency Counseling and Training in Kadu Gede Village Rt.02 and Rt.05 Cilember Village - Khair, Masykur; R, R Herlina; Aisah, Siti; Sarah, Siti; Rahayu, Dikra; Trisna, Rabita; Sekar, Dinda; Mauladi, Muhamad Fadli (Jurnal Pengabdian Kepada Masyarakat Untukmu Nusantara, 2025)
The aim of this service activity is to increase knowledge about emergencies, and increase the knowledge and skills of residents and cadres in providing first aid to people experiencing emergencies. The implementation of this service activity was carried out with an initial survey, providing education about emergencies, training in basic life support, stopping bleeding and how to evacuate, then carrying out event evaluations. It was found that cadres and residents were enthusiastic in demonstrating RJP, and how to evacuate if an emergency occurred. The results of the final evaluation prove that 70.6% of residents and cadres know what RJP means, 64.7% of residents and cadres know first aid for victims or someone experiencing respiratory arrest or cardiac arrest, 94.1% of residents and cadres are late in learning how to evacuate a victim using a stretcher, and 95% of residents and cadres are late in learning how to stop bleeding with 3T (close, press, elevate). This community service activity for cadres and residents of Kadu Gede village, Cilember Village can be said to have had a good impact on increasing residents' knowledge of emergencies and basic life support. Knowledge is the basis for providing information. Keywords: Emergency, BHD, Bleeding, evacuation, residents, cadres